A Narrative Review of the Halal Certification Regulation Dilemma in the Non-Muslim Culinary Business - Gatot Teguh Arifyanto (Jurnal Manajemen Bisnis dan Pariwisata, 2026)
The obligation of halal certification based on Law Number 33 of 2014 concerning Halal Product Assurance places the culinary sector as the epicenter of policy implementation, considering the technical complexity of raw materials, production processes, and recipes that it faces. This complexity is felt especially by non-Muslim culinary business actors, some of whose traditional recipes use non-halal ingredients, thus giving rise to economic, technical, and cultural identity dilemmas. This study aims to explore the response and adaptation strategies of non-Muslim culinary business actors to halal certification obligations, identify specific obstacles faced, and analyze the level of regulatory inclusivity towards the diversity of non-Muslim culinary in Indonesia. The research uses a qualitative method of narrative literature review by synthesizing academic literature, regulatory documents, and relevant supporting sources for the 2014–2026 period. The results of the study show that non-Muslim culinary business actors have pursued various adaptation strategies, such as the substitution of raw materials and the use of self-declaration routes, although they still face layered obstacles in technical aspects (difficulties in substitution of ingredients, risk of cross-contamination), procedural (the obligation of Muslim Halal Supervisors), and socio-cultural (concerns about the loss of ethnic culinary authenticity). The study also found that halal certification regulations are formally inclusive, but still leave gaps at the implementation level that disproportionately burden non-Muslim business actors. The research recommends strengthening the narrative of sharia maqashid as a universal value, flexibility of the Halal Supervisor scheme, and special assistance for the culinary sector as a step to bridge the interests of Muslim consumer protection with the sustainability of non-Muslim group businesses.